A new rainbow gudgeon of Sarcocheilichthys (Teleostei: Cyprinidae) from Fujian Province, China with redescriptions of S. hainanensis - Chen, I-Shiung; Li, Hsien-En (Zootaxa, 2024)
The teleostean family Cyprinidae is a megadiverse fish taxon that occupies most of the freshwater biomes of the world. The cyprinid genus Sarcocheilichthys of the subfamily Gobioninae is represented by a total of 14 nominal species, most of which are distributed in the vast continent of China. Our recent field collections and surveys in river systems of Fujian Province, southern China, had discovered a cyprinid fish that was recognized herein as a Sarcocheilichthys species new to science. The undescribed species, temporarily known as the Hanjiang rainbow gudgeon, is most similar to S. nigripinnis but can be well distinguished by differences in meristic counts, dorsal fin blotch patterns, and the morphology of oromandibular structures and genital organs. A detailed redescription of the valid Hainan rainbow gudgeon, S. hainanensis, is also provided herein.